The 19th Ministerial Council Meeting’s Statement by H.E. Mr. Luvsanvandan BOLD, Minister for Foreign Affairs of Mongolia - Bold, Luvsanvandan (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i17.78 Mongolian Journal of International Affairs, No.17 2012: 9-11